Semiconductor laser with optical feedback: From excitable to deterministic low-frequency fluctuations - Eguia, M.C. (1999)
Semiconductor lasers with optical feedback present a regime in which power dropouts are observed. Although this regime has been extensively studied, there is no agreement about whether the dropouts are deterministically or stochastically generated. In this paper we will study the statistics of time intervals between dropouts assuming noise-driven simple excitable models. We explain the appearance of characteristic times in the first return maps. © 1999 The American Physical Society.